Implementation Penundaan Kewajiban Pembayaran Utang (PKPU) in Bankruptcy Process in Indonesia - Putra, Agung Pratama; Sinaga, Niru Anita; Sudarto, Sudarto (Neolectura, 2025)
Penundaan Kewajiban Pembayaran Utang (PKPU) is a legal mechanism that aims to provide debtors with the opportunity to restructure debts and avoid bankruptcy by preparing a peace plan agreed to by creditors, as stipulated in Law Number 37 of 2004. However, in practice, PKPU in Indonesia does not always run effectively due to various obstacles that arise, including liquidity difficulties and legal pressure from creditors who continue to file homologation cancellation lawsuits and criminal reports against debtors. This research aims to analyze the implementation of PKPU in the bankruptcy process and identify the obstacles faced, with a normative and empirical legal approach through a case study of PT Mahkota Properti Indo Senayan and PT Mahkota Properti Indo Permata. The results of the study indicate that although PKPU can provide a way out of the threat of bankruptcy, its implementation is often hampered by the lack of post-homologation supervision and adequate legal protection for debtors. Therefore, this study recommends strengthening regulations and increasing supervision so that PKPU can become an effective instrument in debt restructuring and supporting the stability of debtors' businesses.